(untitled) (Interdisciplinary Research in Education, 2025)
This study has explored the roles and challenges faced by pre-service teachers during their teaching practicum under the post-positivist research paradigm. A quantitative survey approach was employed using probability sampling to select 85 practicum students at different subjects from M.Ed. level programs at six campuses (Central Department of Education, Mahendra Ratna Campus, Tahachal, Janamaitri Campus, Sano Thimi Campus, Baneshwor Multiple Campus, and Butwal Multiple Campus) constituent and affiliated with Tribhuvan University. Data was collected through Likert-type scale questionnaires, with reliability coefficients of 0.886 and content validity confirmed by educational experts from Tribhuvan University. Statistical analysis was conducted using one-sample t-tests to find effect sizes, to examine perceptions of duties and the extent of challenges encountered. The results showed that preservice teachers are responsible for indispensable tasks such as lesson planning, collaborative instructional design, and fair assessment, all of which contribute to their professional growth. However, these responsibilities are often handled in a theoretical manner due to limited hands-on experience, insufficient collaboration, and a lack of knowledge about inclusive assessment practices. Preservice teachers’ struggles with student diversity and professional identity signal the need for improved training in inclusion, reflection, and practical experience. This study suggests that the teaching practicum must be modified to focus on holistic skill development of pre-service teachers beyond the mere completion of fragmented tasks and theoretical instruction.